Diagnostic and therapeutic value of laparoscopy and video surgery in the acute appendicitis - Salom, Andrés (Cirugía del Uruguay, 2002)
Clinical characteristics of this desease determine that there be a large number of diagnostic errors and unnecessary surgeries, particular/y in young women. The percentage of appendícectomíes on healthy appendíces ranges as hígh as a 10% to a 40% accordíng to varíous publícatíons. Even though mortalíty in appendicectomies has been reduced to practica/ly ni/, the morbility rate is high and is fundamental/y linked with approach, such as infection ot operative wound, the onset of eventrations and the formation ot adherences which engender a symptomatology akin to that of intestinal occ/usion.